Executive Character and Financial Distress on Tax Avoidance with Manager’s Overconfidence as a Moderating Variable - Firmansyah, Aditya; Pratiwi, Adhitya Putri (Jurnal Akuntansi, 2024)
Abstract Purpose - The purpose of this study was to determine the effect of executive character and financial distress on tax avoidance with manager overconfidence as a moderating variable. Design/methodology/approach - This study used a sample of BUMN Companies listed on the Indonesia Stock Exchange in 2017-2021. The data used in this study are financial statements and annual reports. The sampling technique used was purposive sampling, where from 38 BUMN companies, a sample of 10 companies was obtained for 5 years so that a total of 50 data samples were obtained. The analysis used is panel data regression analysis using fixed effect regression model data processed with the help of Eviews9 software. Findings - The results obtained show that simultaneously executive character and financial distress affect tax avoidance. The results obtained show partially that executive character affects tax avoidance, financial distress has no effect on tax avoidance. The results obtained also show that manager overconfidence is not able to moderate the effect of executive character and financial distress on tax avoidance.Research limitations/implications - The independent variables used in this research are only 2 factors, namely executive character and financial distress, as well as a moderating variable, namely manager overconfidence. This allows other factors that influence tax avoidance to be ignored. Keywords: Executive Character, Financial Distress, Tax Avoidance, and Manager Overconfidence